Discover Your Inner Strength: A Positive Psychological Approach to Bolster Resilience and Address Radicalization - Dechesne, Mark; Ahajjaj, Jamal (Frontiers in Psychology, 2021)
The article reports initial attempts to evaluate a new positive psychological approach to bolster resilience among Muslims in the Netherlands. The approach uses Quranic texts and principles from Mental Contrasting and Implementation Intentions (MCII) to encourage Muslims in The Netherlands to reflect in groups on appropriate responses to challenges they are facing. The participants are inspired by Quranic texts and encouraged to write responses to specific challenges in the form of IF-THEN rules, and to practice these IF-THEN rules for several weeks. Two studies indicate that this approach increases personal growth initiative. The implications of these findings for the MCII literature and Preventing/Countering Violent Extremism are discussed.